2017
DOI: 10.1186/s40425-017-0281-y
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitor is active against large cell neuroendocrine carcinoma with high tumor mutation burden

Abstract: BackgroundLarge cell neuroendocrine tumor (LCNEC) of the lung is a rare and aggressive tumor similar to small cell lung cancer (SCLC). Thus, it is often treated similarly to SCLC in the front-line setting with a platinum doublet. However, treatment for patients beyond the first line remains undefined.Case presentationWe report the case of a patient with stage IB LCNEC (PD-L1 negative but positive for PD-L1 amplification and tumor mutation burden high) who progressed after adjuvant chemotherapy after surgery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…To our knowledge, this is the first study that employed ctDNA sequencing in SCLC patients using a large gene panel capable of identifying sufficient mutations for subclonal analysis. Another foreseen advantage of a large gene panel is a more accurate estimation of tumor mutation burden (TMB), a potential biomarker for response to immune checkpoint blockade in many cancer types 37 41 . Recently presented early phase clinical trials have shown encouraging activity of immune checkpoint blockade in treatment of SCLC patients 42 44 , and high TMB has been demonstrated to be associated with superior response and prolonged survival in SCLC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that employed ctDNA sequencing in SCLC patients using a large gene panel capable of identifying sufficient mutations for subclonal analysis. Another foreseen advantage of a large gene panel is a more accurate estimation of tumor mutation burden (TMB), a potential biomarker for response to immune checkpoint blockade in many cancer types 37 41 . Recently presented early phase clinical trials have shown encouraging activity of immune checkpoint blockade in treatment of SCLC patients 42 44 , and high TMB has been demonstrated to be associated with superior response and prolonged survival in SCLC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients stopped treatment due to disease progression, 1 due to pulmonary interstitial pneumonia [44]. A case report described a heavily pretreated patient with PD-L1-positive LCNEC stage IB who achieved a significant and durable response with pembrolizumab [45]. …”
Section: Clinical Experience With Checkpoint Inhibitors In Nensmentioning
confidence: 99%
“…reported a single case of pulmonary LCNEC in 2017 with an exceptional response to a first dose of pembrolizumab. The patient was continuing treatment at the time of publication of the case study so the duration of response cannot be determined [ 3 ].…”
Section: Resultsmentioning
confidence: 99%